2000
DOI: 10.1172/jci8623
|View full text |Cite
|
Sign up to set email alerts
|

The role of the LDL receptor in apolipoprotein B secretion

Abstract: IntroductionThe LDL receptor plays a critical role in the regulation of plasma LDL levels by mediating approximately two thirds of LDL clearance (1-3). Loss of LDL receptor function leads to decreased LDL catabolism and elevated LDL levels (4). LDL receptor levels are affected by diet, hormones, and most dramatically, by mutations in the LDL receptor locus that lead to familial hypercholesterolemia (FH).Early studies of LDL metabolism in patients with FH revealed that in addition to the LDL clearance defect, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
177
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(210 citation statements)
references
References 91 publications
28
177
1
2
Order By: Relevance
“…We recently demonstrated that the presence of the LDLR greatly increases the proportion of apoB subject to presecretory degradation. Our results directly link VLDL overproduction in FH with the loss of the LDLR (6).…”
Section: Mutations In the Low Density Lipoprotein (Ldl) Receptor (Ldlr)supporting
confidence: 55%
“…We recently demonstrated that the presence of the LDLR greatly increases the proportion of apoB subject to presecretory degradation. Our results directly link VLDL overproduction in FH with the loss of the LDLR (6).…”
Section: Mutations In the Low Density Lipoprotein (Ldl) Receptor (Ldlr)supporting
confidence: 55%
“…In the absence of PCSK9, it seems that there is reduced apoB48 secretion from mouse primary hepatocytes. The increase in LDLR protein expression resulting from the deletion of Pcsk9 could explain this observation by means of the mechanism described by Twisk et al (24), who previously demonstrated that the LDLR protein can mediate posttranslational presecretory degradation of apoB in hepatocytes. A second possibility is that increased LDLR expression on the cell surface mediates immediate VLDL recapture, thus reducing total apoB secretion into the medium.…”
Section: Discussionmentioning
confidence: 88%
“…To better assess how well our calculations agreed with these experimental results, we performed a literature search for similar pulse-chase experiments involving 35 Cys and 35 Met labelling in which error bars are reported for proteins translating in vivo. The error bars were extracted from the published graphs of three separate studies [49][50][51] n (ref. 52).…”
Section: Methodsmentioning
confidence: 99%